2019
DOI: 10.1021/acs.organomet.9b00575
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot, One-Step Precatalysts through Mechanochemistry

Abstract: The development and implementation of transition-metal-based precatalysts have played crucial roles in modern organic synthesis. However, while the use of such species greatly improves sustainability, their preparative routes often rely on multiple time-, energy-, and solvent-intensive steps. By leveraging solvent-free mechanochemical synthesis through vibratory ball milling, we report the one-pot, one-step synthesis of a range of first-row transition-metal bis­(imino)­pyridine complexes, where both the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…The influence of mechanical forces on chemical reactions has attracted chemists for many decades, for instance, due to the possibility of opening alternative synthetic pathways otherwise unachievable using different means of energetic input, such as light and temperature. [1][2][3][4] The field of mechanochemistry 5 has experienced enormous advances in the past years, reflected in versatile chemical and biological applications (for selected reviews see [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ), ranging from the solid-state synthesis of inorganic materials, [24][25][26][27] metal-organic [28][29][30][31][32] and organic compounds, [33][34][35][36] covalent organic frameworks, 37 and polymers [38][39][40][41][42][43] to enzymatic reactions 19,[44][45]…”
Section: Introductionmentioning
confidence: 99%
“…The influence of mechanical forces on chemical reactions has attracted chemists for many decades, for instance, due to the possibility of opening alternative synthetic pathways otherwise unachievable using different means of energetic input, such as light and temperature. [1][2][3][4] The field of mechanochemistry 5 has experienced enormous advances in the past years, reflected in versatile chemical and biological applications (for selected reviews see [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] ), ranging from the solid-state synthesis of inorganic materials, [24][25][26][27] metal-organic [28][29][30][31][32] and organic compounds, [33][34][35][36] covalent organic frameworks, 37 and polymers [38][39][40][41][42][43] to enzymatic reactions 19,[44][45]…”
Section: Introductionmentioning
confidence: 99%
“…Mechanosynthesis is an attractive alternative to conventional solution-based synthesis, since it not only addresses several environmental concerns associated with the use of large volume of solvents but also often offers shorter reaction times and higher yields. , Uniquely, mechanochemistry also offers opportunities to prepare chemical compounds that are otherwise difficult or impossible to prepare by solution methods owing to limited solubility of the starting material and the limited stability of the product in solution. , In recent years, mechanochemistry has increasingly been applied as a solvent-free (or nearly solvent-free) synthetic route in a wide range of fields. (e.g., organometallic complexes, organo-catalysts, cocrystals, metal–organic frameworks, alloys, composites, , etc . )…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bantreil et al recently reported the mechanochemical synthesis of half-sandwich ruthenium complexes with N-heterocyclic carbene (NHC) and [Ru­( p -cymene)­(μ-Cl)­Cl] 2 , in situ obtaining the Ag-NHC complex with only a small amount of water (0.3 μL/mg of reactants) . Jurca and co-workers reported the mechanochemical synthesis of bis­(imino)­pyridine-MX 2 (M = Mn, Fe, Co, Ni, Cu, Zn; X = Cl, Br) complexes via a one-pot, one-step process from diacetylpyridine, panisidine, and a MX 2 precursor in the presence of MgSO 4 and p -toluenesulfonic acid …”
Section: Introductionmentioning
confidence: 99%
“…31 Jurca and co-workers reported the mechanochemical synthesis of bis(imino)pyridine-MX 2 (M = Mn, Fe, Co, Ni, Cu, Zn; X = Cl, Br) complexes via a one-pot, one-step process from diacetylpyridine, panisidine, and a MX 2 precursor in the presence of MgSO 4 and p-toluenesulfonic acid. 32 Following our interest in studying half-sandwich metal complexes' catalytic activities with diverse functional ligands, 33−37 we report herein an efficient and more sustainable method to synthesize a new, previously unreported halfsandwich ruthenium complex 2, to the best of our knowledge. Complex 2 bears an aldehyde functional group that can enable postsynthetic modification, which could be carried out via a mechanochemical Wittig reaction.…”
Section: ■ Introductionmentioning
confidence: 99%